International relations and the problem of difference - Inayatullah, Naeem (Global horizons., 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other.